Hypersialylation is a common feature of neurofibrillary tangles and granulovacuolar degenerations in Alzheimer's disease and tauopathy brains. Issue 4 (21st December 2015) - Nagamine, Shun; Yamazaki, Tsuneo; Makioka, Kouki; Fujita, Yukio; Ikeda, Masaki; Takatama, Masamitsu; Okamoto, Koichi; Yokoo, Hideaki; Ikeda, Yoshio
Abstract : Glycosylation is one of the major post‐translational modifications of proteins. The status of sialylation of the neuropathological hallmarks of various neurodegenerative disorders was investigated in this study. Here, we report the novel findings that two phosphorylated tau (p‐tau)‐containing structures associated with Alzheimer's disease (AD), that is, neurofibrillary tangles (NFTs) and granulovacuolar degenerations (GVDs), were hypersialylated. The NFTs, GVDs and dystrophic neurites of senile plaques (SPs) in AD hippocampi were clearly visualized by immunohistochemistry using an anti‐sialic acid (SA) antibody. In contrast, the amyloid core of SPs was not sialylated at all. Interestingly, other p‐tau‐containing structures, that is, globose‐type NFTs in progressive supranuclear palsy and Pick bodies and ballooned neurons in frontotemporal lobar degeneration with Pick bodies, were also hypersialylated. Unlike the p‐tau‐containing structures observed in tauopathies, the hallmarks of other neurodegenerative disorders, such as Lewy bodies in Parkinson's disease, glial cytoplasmic inclusions in multiple system atrophy, Bunina bodies, skein‐like inclusions and round inclusions in amyotrophic lateral sclerosis, intranuclear inclusions in neuronal intranuclear inclusion disease and physiological bodies or granules (lipofuscin granules, corpora amylacea and melanin granules), were not immunolabeled by the anti‐SA antibody. Because this antibody specifically identified NFTs and GVDs, immunostaining for sialylation represents a useful tool to screen these structures in a diagnostic setting. These results clearly indicate that the pathological hallmarks of various tauopathies are commonly hypersialylated, and that sialylation plays an important role in the process of p‐tau accumulation in AD and other tauopathies.